2022
DOI: 10.3390/children9091280
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Indirect and Direct Laryngoscopes in Pediatric Patients: A Systematic Review and Network Meta-Analysis

Abstract: This research aimed to produce a coherent ranking of the effectiveness of intubation devices in pediatric patients using network meta-analysis (NMA). We searched the electric databases for prospective randomized studies that compared different tracheal intubation devices in pediatric patients. The primary outcome was intubation failure at the first attempt. Secondary outcomes were glottic visualization and intubation time. The statistical analysis performed used DerSimonian and Laird random-effects models. Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…However, there are huge individual differences in the growth and development of children. Since the organ catheter model can't be accurately selected, repeated intubation attempts are needed to determine the optimal model of endotracheal tube (ETT) [4][5][6]. During this period, it is easy to induce hypoxemia, air leakage, re ux aspiration, and even laryngeal tissue damage; in severe cases, it will also lead to cardiac arrest.…”
Section: Backgroudmentioning
confidence: 99%
“…However, there are huge individual differences in the growth and development of children. Since the organ catheter model can't be accurately selected, repeated intubation attempts are needed to determine the optimal model of endotracheal tube (ETT) [4][5][6]. During this period, it is easy to induce hypoxemia, air leakage, re ux aspiration, and even laryngeal tissue damage; in severe cases, it will also lead to cardiac arrest.…”
Section: Backgroudmentioning
confidence: 99%
“…Additionally, White et al reported that Airtraq significantly prolonged intubation time compared to direct laryngoscopes [10]. Furthermore, a previous network meta-analysis comparing indirect and direct laryngoscopes in pediatric patients reported that there were no significant differences between the two laryngoscopes in terms of success rate, intubation time, and glottic visualization in tracheal intubation [11,12]. However, this report did not focus on patients with difficult airways, so the usefulness of the indirect laryngoscope in pediatric patients with difficult intubation is not known.…”
Section: Introductionmentioning
confidence: 99%